PENGEMBANGAN AKTIVITAS FINGER PAINTING DENGAN METODE KELOMPOK UNTUK MEMFASILITASI PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI SPS TAAM NURUL AMIN - Ririn Nur Afifah, - (2022)
This research is a research on the development of finger painting activities with the group method to facilitate the socio-emotional development of early childhood. Because of the importance of developing the social emotional aspects of early childhood and developing PAUD learning programs to facilitate children's development, the researchers designed finger painting activities with group meotes to facilitate the social emotional development of children aged 5-6 years at SPS TAAM Nurul Amin. The purpose of this study is to describe the basic needs for developing finger painting activities with the group method to facilitate the social emotional development of early childhood, to describe the design of developing finger painting activities with the group method to facilitate the social emotional development of early childhood, and to describe the trial process and product feasibility results. finger painting activity development design with the group method to facilitate the social emotional development of early childhood. This study uses the Educational Design Research (EDR) research method from Mc Kenny & Reaves (2012) with research stages including: 1) Analysis and Exploration; 2) Design and Construction; and 3) Evaluation and Reflection. Data collection techniques in this study are interviews, observation, questionnaires and validation. The design was validated by art development experts, social emotional development experts and pedagogical experts then tested twice and packaged into a guide book. Based on the results of the analysis of the test and the teacher's response to the product, finger painting activities with the group method can facilitate the social emotional development of early childhood in school and the product is suitable for use in Early Childhood Education.